A novel scorpine-like peptide from the amazonian scorpion Brotheas amazonicus with cytolytic activity - Reis, Mouzarllem Barros; De Castro Figueiredo Bordon, Karla; Martins, Jonas Gama; Wiezel, Gisele Adriano; Cipriano, Ualter Guilherme; Emerson de Lima Procópio, Rudi; Deperon Bonato, Vania Luiza; Arantes, Eliane Candiani (Frontiers in Pharmacology, 2025)
IntroductionScorpion venoms contain bioactive molecules with potential antitumor properties. This study aimed to evaluate the cytotoxic effects of crude Brotheas amazonicus venom (BamazV) and its molecular weight–separated fractions on human breast cancer cell lines, with a focus on identifying active compounds and elucidating their mechanisms of action.MethodsHuman breast epithelial (MCF10A) and breast cancer cell lines (SKBR3, MCF7, and MDA-MB-231) were first assessed for dose-dependent responses to paclitaxel, a standard chemotherapeutic agent. BamazV was fractionated by ultrafiltration into >10 kDa, 3–10 kDa, and <3 kDa fractions, which were tested for cytotoxic activity. The active fraction underwent reversed-phase chromatography, and the major bioactive peptide was characterized by mass spectrometry and Edman degradation. Cytotoxic mechanisms were investigated using cell death assays.ResultsAll cell lines showed a dose-dependent response to paclitaxel. Crude BamazV induced significant cytotoxicity at concentrations ≥ 50 μg/mL, with triple-negative MDA-MB-231 cells being the most sensitive. The >10 kDa fraction retained cytotoxic activity, leading to the isolation of a major peptide, BamazScplp1. Sequence analysis revealed 46–55% identity and 74–81% similarity to known scorpine-like peptides. Functional assays indicated that BamazScplp1 induced predominantly necrotic cell death, consistent with the activity profile of previously reported cytolytic scorpine-like molecules.DiscussionThese findings identify BamazScplp1 as a scorpine-like peptide with selective cytotoxicity toward triple-negative breast cancer cells, underscoring the potential of B. amazonicus venom as a source of bioactive compounds for cancer research.